Tethered swimming as an useful tool to measure unbalance between arms and force production decrease - Morouco, P. G.; Marinho, D. A.; Fernandes, R. J.; Marques, M. C. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Our aim of present study was to investigate the differences in force production between arms during front crawl tethered swimming (TS). Firstly, 14 young male swimmers (14.2 ± 1.09 yrs; 168.3 ± 2.22 cm; 59.9 ± 4.77 kg) undertook a 30 s maximum front crawl TS test. It was observed that preferred arm (P_Fmax) produces a maximum force higher than non-preferred arm (NP_Fmax). Additionally, was verified that the decrease in maximum force was higher for P_Fmax than NP_Fmax. In the second part of the study, 6 elite male swimmers (19.8 ± 2.23 yrs; 183.6 ± 3.64 cm; 77.3 ± 3.64 kg) replicated the methodology, being the individual curves assessed trough polynomial curves, which allowed identifying the unbalance between arms. This methodology may detect a limiting factor of performance being a useful tool for coaches training prescription.